The role of chronotype, gender, test anxiety, and conscientiousness in academic achievement of high school students - Rahafar, Arash; Randler, Christoph (Chronobiology international, 2016)
Previous findings have demonstrated that chronotype (morningness/intermediate/eveningness) is correlated with cognitive functions, that is, people show higher mental performance when they do a test at their preferred time of day. Empirical studies found a relationship between morningness and higher learning achievement at school and university. However, only a few of them controlled for other moderating and mediating variables. In this study, we included chronotype, gender, conscientiousness and test anxiety in a structural equation model (SEM) with grade point average (GPA) as academic achievement outcome. Participants were 158 high school students and results revealed that boys and girls differed in GPA and test anxiety significantly, with girls reporting better grades and higher test anxiety. Moreover, there was a positive correlation between conscientiousness and GPA (r = 0.17) and morningness (r = 0.29), respectively, and a negative correlation between conscientiousness and test anxiety (r = -0.22). The SEM demonstrated that gender was the strongest predictor of academic achievement. Lower test anxiety predicted higher GPA in girls but not in boys. Additionally, chronotype as moderator revealed a significant association between gender and GPA for evening types and intermediate types, while intermediate types showed a significant relationship between test anxiety and GPA. Our results suggest that gender is an essential predictor of academic achievement even stronger than low or absent test anxiety. Future studies are needed to explore how gender and chronotype act together in a longitudinal panel design and how chronotype is mediated by conscientiousness in the prediction of academic achievement.
Published online: 10 Dec 2015
Gesehen am 27.01.2021